JURIDICAL ANALYSIS OF IMPLEMENTING THE PRESIDENTIAL THRESHOLD IN THE PRESIDENTIAL ELECTION OF INDONESIA - Mubarik Rahmayanti; Irfan Amir (IAIN Bone, 2021)
Since issuing the Constitutional Court Decision Number 14/PUU-XI/2013, the general election design must be carried out simultaneously between the election of legislative members and the election of the President and Vice President (Pilpres). Article 6A Paragraph (2) of the 1945 Constitution mandates that pairs of candidates for President and Vice-President are proposed by political parties or coalitions of political parties taking part in the general election prior to implementing the general election. Accordingly, in order to strengthen the presidential system, pairs of candidates proposed in the presidential election are required to meet the